Factors Associated with School Effectiveness: Detection of High- and Low-Efficiency Schools through Hierarchical Linear Models - Jesús García-Jiménez; Juan-Jesús; Javier Rodríguez-Santero (MDPI AG, 2022)
School effectiveness is a topic of interest addressed by numerous research projects focused on clarifying which variables contribute to the explanation of educational performance. This research aims to find out to what extent social, cultural, and academic variables at the student and school levels, as perceived by families, influence performance, and to evaluate the relevance of high residual and gross score criteria in the selection of effective or ineffective schools. Census data from diagnostic evaluations of the Mathematical Reasoning and Linguistic Communication of students in a certain Spanish region, over five academic years, have been used. The multilevel hierarchical analyses carried out have enabled the detection of centers of high and low efficiency, as well as the identification of which factors, related to the idiosyncrasy of the students and the educational center they attend, significantly influence the performance of the students. It was concluded that the socioeconomic and cultural level of the families, the family expectations, the commitment to reading and the educational agreement were significant variables in the explanation of the students' educational performance, and that the residual score of the educational centers was a valid criterion to estimate their level of effectiveness once the socio-cultural factors have been controlled.